Antioxidant, anti-obesity, and lipid-lowering properties of Philippine "duhat" (Syzgium cumini L. skeel) freeze-dried fruit flesh - Mercado, Carmela Jhoy G.; Atienza, Liezl M.; Sunico, Dianne Jane A.; Maniwang, Jonna Rose C.; Gapasin, Roxanne P.; Gaban, Prince Joseph V.; Castillo-Israel, Katherine Ann T.; Cena-Navarro, Rohani; Estacio, Maria Amelita C. (2021)
"Philippine indigenous berries are known as rich sources of antioxidants that may promote health and prevent the occurrence of diseases. Thus, the study investigated the nutritional, antioxidants, anti-obesity, and lipid-lowering properties of freeze-dried "duhat" (FDD) (Syzgium cumini L. Skeel) fruit using proximate analysis, in vitro antioxidant assays, and in vivo efficacy using obese diet-induced ICR mice, respectively"-Title page.
Includes bibliographical references.
Keywords: Antioxidants; Obesity